The Position of the Indonesian Council of Ulama in The Indonesian State Governmental Legal System: The Perspective of Abū Ḥasan al-Māwardī - Mahendra, Sandya; Junaidi, Muhammad (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
This study aims to describe the position of the Indonesian Council of Ulama (MUI) in the Indonesian constitutional law system and to describe the MUI’s position in Abū Ḥasan al-Māwardī’s thought. The method in this study uses normative legal research or doctrinal law with a philosophical, historical and conceptual approach. If viewed from a state institutional perspective, the MUI is in the realm of the political infrastructure area. Political Infrastructure itself is a group of institutions that exist in society. The MUI fatwa is not a type of statutory regulation that has binding legal force Based on Article 1 point 2, Article 7 paragraph (1) and Article 8 paragraph (1) of Law 12/2011, the MUI fatwa is not statutory regulation, because it is not made by an authorized body or institution and does not have general binding power. However, the MUI fatwas are a source of material law. To become a positive law, the MUI fatwa must be positivized by the state through statutory regulations. The theory of state objectives developed by Al-Mawardi has two basic concepts, namely (1) formalization of Shariah activities, (2) regulation of social, economic, political, legal and military activities.